Unveiling the potency of polymers and their environmental implications: an agricultural perspective - Debadatta Sethi; Sanjib Kumar Sahoo; Prava Kiran Dash; Shraddha Mohanty; Kiran Kumar Mohapatra; Kshitipati Padhan; Konathala Kusumavathi; Narayan Panda; Sushanata Kumar Pattanayak (Discover Soil)
Abstract Polymers application in agriculture is increasing day by day to enhance the crop productivity, improve soil quality and conserve water resources. In places where water is scarce, superabsorbent polymers (SAPs) can be used as they help retain the soil moisture which in turn increases the moisture resilience of plants. These controlled-release polymers are beneficial in the agrochemical application since the amount used is reduced which cuts down pollutants entering the environment. However, problems come into play with the use of synthetic polymers mainly with the microplastic pollution which affects the porosity of soil. The environmental risk associated with polymers, including the persistence of microplastic and their long-term effects on ecosystems need to be carefully addressed. While current forms of polymer extraction and soil analysis such as density separation and chemical extraction still require consistency however, the methods are promising. To mitigate these risks, further research is needed to reduce the environmental persistence of polymers especially the microplastics. The SAPs require more research in order to reduce the risk of the polymers having adverse consequences on the quality of soil and water in the future. This review looks into the advance polymer materials used in today’s agriculture and their applications in improving the soil environment and the agricultural productivity. The paper discusses both the beneficial and adverse impacts of the use of polymers in agricultural practices as well as the environmental impacts advocating for the sustainable use of the chemicals.